Study on the mechanism of coal pillar breaking and fracture development under repeated mining in a close seam group - Teng, Fei; Yu, Minggao; Han, Xuefeng; Chao, Jiangkun (Frontiers in Earth Science, 2023)
The study show the influence of coal mining on pillar under a repeated mining, in a close coal seam group, the fracture and instability process and influence mechanism of fracture development on the oxidation of coal pillars. In this paper, FLAC3D numerical simulation software is used to simulate the dynamic evolution characteristics of stress, displacement of the upper coal pillar. The results show that 1) The theoretical length of the fracture along the strike of the upper coal pillar is obtained by establishing the mechanical model of the upper coal pillar, which is consistent with the numerical simulation results. 3) In this paper, according to the dynamic evolution characteristics of displacement and stress on the coal pillar, the coal pillar is divided into the “step subsidence area”, “fracture compaction area” and “reverse stress area”, and the high risk area of the coal spontaneous combustion is determined.